Perceptions of the existence of museums for vocational students in understanding history learning objectives - Merina, Merina; Mushoddik, Mushoddik; Qodariah, Lelly; Pratama, Cahya Adhitya (Program Pascasarjana Universitas Negeri Yogyakarta, 2023)
Museums have historical collections, so it is appropriate to use museums as a source of learning media in learning history. In the learning process, the purpose of learning history is to shape the character of the nation, where this character must grow at all levels of education, both elementary, junior high, high school, and vocational school, as a provision for students to make them the next generation of the nation with good character. This study aims to analyze the perceptions of SMK As-Salam students toward the existence of museums to understand the purpose of learning history. The research method used in this research is the descriptive qualitative research method. The data collection techniques used are observation, documentation, and interviews. The results showed that all students, especially vocational students, need to learn history through museums to understand historical learning by directly seeing the relics of history. Hopefully, this research can be useful for further literature on history lessons in vocational schools.